Expression of TRAIL and death receptor DR4 in Palmer type 2 TFCC lesions - Unglaub, Frank; Thomas, Susanne Barbara; Kröber, Markus; Dragu, Adrian; Fellenberg, Jörg; Mittlmeier, Thomas; Wolf, Maya Barbara; Horch, Raymund (Archives of orthopaedic and trauma surgery, 2010)
Degenerative articular disc perforations of the triangular fibrocartilage (TFC) of the wrist are characterized by fibrocartilage cell loss and are often associated with ulna-plus situations. Apoptosis has been found to play a crucial role in fibrocartilage cell loss, however, the molecular mechanism and mediators are still poorly understood.